Water security in India : hope, despair, and the challenges of human development - Asthana, Vandana; Shukla, A. C. (Ashok Chandra), 1942- (New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2014)
"Few people actively engaged in India's water sector would deny that the Indian subcontinent faces serious problems in the sustainable use and management of water resources. Water resources in India have been subjected to tremendous pressures from increasing population, urbanization, industrialization, and modern agricultural methods. The inadequate access to clean drinking water, increase in water related disasters such as floods and droughts, vulnerability to climate change and competition for the resource amongst different sectors and the region poses immense pressures for sustainability of water systems and humanity. Water Security in India addresses these issues head on, analyzing the challenges that contemporary India faces if it is to create a water-secure world, and providing a hopeful, though guarded, road-map to a future in which India's life-giving and life-sustaining fresh water resources are safe, clean, plentiful, and available to all, secured for the people in a peaceful and ecologically sustainable manner"--
Includes bibliographical references (pages 346-380) and index.
Keywords: WATER SECURITY -- India; WATER-SUPPLY -- Inida -- Management; WATER RESOURCES DEVELOPMENT -- Government policy -- India; POLITICAL SCIENCE --PUBLIC POLICY; POLITICAL SCIENCE--ECONOMIC POLICY